Plato «Cratylus»: An ancient dialogue with modern sophists (true names and false names) - Sivertsev, Eugenio; Díaz, Roxana (Contrastes. Revista Internacional de Filosofía, 2017)
The article discusses Plato’s theory of language, in the form as it is presented in the Cratylus dialogue. The article elaborates on Plato’s idea that words designate the nature of things they name if the language is used in the correct way. The authors suppose that Plato’s methodology of the interpretation of words can be applied for analyzing self-consciousness of modern man who lives in the era when the traditional ethical values are in crisis.